Coronary CT Angiography in Coronary Artery Disease: Correlation between Virtual Intravascular Endoscopic Appearances and Left Bifurcation Angulation and Coronary Plaques - Sun, Zhonghua (Hindawi Publishing Corporation, 2013)
The aim of this study is to investigate the relationship between intraluminal appearances of coronary plaques and left coronary bifurcation angle and plaque components using coronary CT virtual intravascular endoscopy (VIE). Fifty patients suspected of coronary artery disease undergoing coronary CT angiography were included in the study. The left bifurcation angle in patients with diseased left coronary artery which was measured as 94.3°± 16.5 is significantly larger than that in patients with normal leftcoronary artery, which was measured as 76.5°± 15.9 (P < 0.001). Irregular VIE appearances were found in 10 out of 11 patients with mixed plaques in the left anterior descending (LAD) and left circumflex (LCx), while, in 29 patients with calcified plaques in the LAD and LCx, irregular VIE appearances were only noticed in 5 patients. Using 80° as a cut-off value to determine coronary artery disease, smooth VIE appearances were found in 95% of patients (18/19) with left bifurcation angle of less than 80°, while irregular VIE appearances were observed in nearly 50% of patients (15/31) with left bifurcation angle of more than 80°. This preliminary study shows that VIE appearances of the coronary lumen are directly related to the types of plaques.